Capsular expansion after ultrasound-guided injection of the hip as parameter of efficacy: description of technique and report of preliminary data - Calogero Corsello (Verduci Editore, 2020)
The infiltration procedure with hyaluronic acid has proven to be effective and safe in the integrated multimodal therapy of hip osteoarthritis. Ultrasound represents a diagnostic and therapeutic support to the infiltration procedure; it is hence possible to carry out an appropriate study of the hip in the pre-infiltration phase. Through ultrasound-guiding, the infiltration therapy can be performed with precision, safety, and maximum comfort for the patient. Ultrasound imaging allows us to study the capsular space and the identification of the capsular line, and after the introduction of hyaluronic acid, the capsular expansion of the hip can be a parameter of treatment efficacy. This study evaluates the extent of capsular expansion of the hip in ultrasound after infiltration therapy and its correlation with a positive outcome.